Hubungan Antara Tingkat Pengetahuan Ibu Tentang Gizi Dengan Status Gizi Anak Di Sd Citra Kasih Manado - Evangelin Chrisanty Kurniawan; Shirley Everdinna Susanna Kawengian; Alexander Sam Leonard Bolang (Syntax Idea)
Good nutritional status, which is related to children’s food consumption, can improve physical and academic development. Maternal knowledge of nutrition may affect the quality of the children’s diet. Maternal knowledge of nutrition can be related to the elementary school aged children’s nutritional status. This study aim to analyze the relationship between maternal knowledge of nutrition and children’s nutritional status at Citra Kasih Elementary School in Manado. This is a quantitative analytic study design with Cross-Sectional approach. This study involved 72 respondents and used Chi Square statistic analysis. The datas used in this study was obtained through Google Form based questionnaire and anthropometric measurement of weight and height of the children. The result showed that there was a significant relationship between maternal knowledge of nutrition and the nutritional status of children (p=0,004). The maternal knowledge of nutrition consist of 3 levels, lacking, enough, and good. The nutritional status consist of good and bad nutritional status. There was very significant relationship between maternal knowledge of nutrition and the nutritional status at Citra Kasih Elementary School Manado. It is recommended for mothers to improve their nutritional knowledge to maintain or improve their children’s nutritional status